Surface Roughness and Grain Size Characterization of Annealing Temperature Effect For Growth Gallium and Tantalum Doped Ba0.5 Sr0.5TiO3Thin Film - Irzaman Irzaman; H. Darmasetiawan; H. Hardhienata; M. Hikam; P. Arifin; S.N. Jusoh; S. Taking; Z. Jamal; M.A. Idris (PPIKSN-BATAN, 2009)
Thin films 10 % gallium oxide doped barium strontium titanate (BGST) and 10 % tantalum oxide doped barium strontium titanate (BTST) were prepared on p-type Si (100) substrates using chemical solution deposition (CSD) method with 1.00 M precursor. The films were deposited by spin coating method with spinning speed at 3000 rpm for 30 seconds. The post deposition annealing of the films were carried out in a furnace at 200oC, 240oC, 280oC (low temperature) for 1 hour in oxygen gas atmosphere. The surface roughness and grain size analysis of the grown thin films are described by atomic force microscope (AFM) method at 5000 nm x 5000 nm area. The rms surface roughness BGST thin films at 5000 nm x 5000 nm area are 0.632 nm, 0.564 nm, 0.487 nm for temperature 200oC, 240oC, 280oC, respectively, whereas the grain size (mean diameter) are 238.4 nm, 219.0 nm, 185.1 nm for temperature 200oC, 240oC, 280oC, respectively. In fact, to increase annealing temperature from 200oC to 280oC would result in decreasing the rms roughness and grain size. Therefore, rms roughness and grain size would have the strong correlation annealing temperature. Received: 9 November 2008; Revised: 24 August 2009; Accepted: 25 August 2009